Desperate times call for desperate measures the impact of job insecurity on workplace cheating behavior - Ye, Yijiao; Liu, Xinyu; Wu, Long-Zeng; Cheng, Xuan-Mei; Kwan, Ho Kwong (2025)
Cheating is prevalent in workplaces and has a significant detrimental impact, and thus considerable scholarly research has been dedicated to investigating its antecedents. While various influential factors (e.g., performance pressure, perceived threats of COVID-19, leadership, and employee characteristics) have been identified, the effects of employment conditions remain relatively underexplored. We extend the research by applying impression management theory to examine how perceived job insecurity contributes to workplace cheating behavior. Through a field survey and an experimental study, we found that impression management motives mediate the positive link between job insecurity and workplace cheating behavior. In addition, job immobility exacerbates the direct effect of job insecurity on impression management motives, which in turn increases workplace cheating behavior. The findings enrich the literature by identifying job insecurity as a critical employment-related antecedent of workplace cheating behavior and by developing a comprehensive impression management framework to elucidate whether, how, and when job insecurity may result in such behavior.
Keywords: Criminal Behavior; Deviance; Impression management motives; Industrial Psychology; Job immobility; Job insecurity; Occupational Health Psychology; Organizational Psychology; Work and Organizational Psychology; Workplace cheating behavior; Aufsatz in Zeitschrift